A Brief Introduction to Turbidite Channel Depositional Systems - Zhang, Ganggui; Wu, Yupeng; Zhao, Run (Scientific Journal of Technology, 2025)
This article provides a detailed introduction to the concept, formation process, regional division, and depositional characteristics of deep-water turbidite depositional systems. Turbidity currents are sediment gravity flows characterized by turbulence, which mainly occur in deep water areas below the wave base. The depositional system can be divided into three regions: upstream convergent channels, midstream deep-water channels, and downstream terminal fans. The upstream area is dominated by sand-rich sediments, but lacks effective sealing layers; the midstream area develops a single supply channel complex, forming natural levee deposits; the downstream area has a weakly restricted channel network system, with frequent avulsions forming sand-rich overbank deposits. In addition, the article also discusses the oil and gas reservoir potential of different depositional facies, pointing out that channels filled with high-density turbidite facies have better reservoir properties, while channels filled with debris flow facies have poor reservoir properties. Overall, this article provides a comprehensive analysis and description of deep-water turbidite depositional systems, and has important reference value for research and exploration in related fields.